Budgetary management as a determining factor of profitability in hotel companies in Peru (2012 - 2016) - Perez Carrasco, Mara (2018)
Objective: The budget is an important financial management tool for any organization; in this sense, the objective of this research work is to determine if budget management is a determining factor in improving the profitability of hotel companies in Peru. Material: The material is from a primary source, obtained from the results of surveys, interviews and documentary information. The type of research considered the descriptive, explanatory, and non-experimental methodology. Results: The results determine that the national hotel businessmen in Peru fail to observe basic financial tools, among others, the budget structure, which could allow them an adequate financial planning. There is an absence of entrepreneurial training and lack of permanent discipline in auditing which limits their actions and competitiveness and therefore its patrimonial growth. Conclusions: It is concluded that the financial management strategy of the San Luis Hotel Chain during the period of analysis through the use of budget management demonstrates the consistency of its application to enable the profitability on the objectives to be achieved. There is a directional relationship between the management audit procedures and the timely treatment in the presentation of budget deviations that could arise during management.